Making the Grade: The Sensitivity of Education Program Effectiveness to Input Choices and Outcome Measures - Kerwin, Jason; Thornton, Rebecca (Jason Kerwin, 2020)
Keywords: C:Uganda; NULP; ___working_potential_duplicate

Making the Grade: The Sensitivity of Education Program Effectiveness to Input Choices and Outcome Measures - Kerwin, Jason; Thornton, Rebecca L. (SSRN Electronic Journal, 2018)
Keywords: _C:Australia AUS; _C:Chad TCD; _C:Ecuador ECU; _C:India IND; _C:Kenya KEN; _C:Mexico MEX; _C:Spain ESP; _C:Tanzania TZA; _C:Uganda UGA; _C:United States USA; __C:scheme:1

Making the Grade: The Sensitivity of Education Program Effectiveness to Input Choices and Outcome Measures - Kerwin, Jason T.; Thornton, Rebecca L. (The Review of Economics and Statistics, 2021)
This paper demonstrates the acute sensitivity of education program effectiveness to the choices of inputs and outcome measures, using a randomized evaluation of a mother-tongue literacy program. The program raises reading scores by 0.64 SD and writing scores by 0.45 SD. A reduced-cost version instead yields statistically insignificant reading gains and some large negative effects (−0.33 SDs) on advanced writing. We combine a conceptual model of education production with detailed classroom observations to examine the mechanisms driving the results; we show they could be driven by the program initially lowering productivity before raising it, and potentially by missing complementary inputs in the reduced-cost version.

Making the Grade: The Sensitivity of Education Program Effectiveness to Input Choices and Outcome Measures - Kerwin, Jason T.; Thornton, Rebecca L. (The Review of Economics and Statistics, 2021)
This paper demonstrates the acute sensitivity of education program effectiveness to the choices of inputs and outcome measures, using a randomized evaluation of a mother-tongue literacy program. The program raises reading scores by 0.64 SD and writing scores by 0.45 SD. A reduced-cost version instead yields statistically insignificant reading gains and some large negative effects (−0.33 SDs) on advanced writing. We combine a conceptual model of education production with detailed classroom observations to examine the mechanisms driving the results; we show they could be driven by the program initially lowering productivity before raising it, and potentially by missing complementary inputs in the reduced-cost version.

Making the Grade: The Sensitivity of Education Program Effectiveness to Input Choices and Outcome Measures - Kerwin, Jason T.; Thornton, Rebecca L. (The Review of Economics and Statistics, 2020)
This paper demonstrates the acute sensitivity of education program effectiveness to the choices of inputs and outcome measures, using a randomized evaluation of a mother-tongue literacy program. The program raises reading scores by 0.64SDs and writing scores by 0.45SDs. A reduced-cost version instead yields statistically-insignificant reading gains and some large negative effects (-0.33SDs) on advanced writing. We combine a conceptual model of education production with detailed classroom observations to examine the mechanisms driving the results; we show they could be driven by the program initially lowering productivity before raising it, and potentially by missing complementary inputs in the reduced-cost version.
Keywords: NULP; ___working_potential_duplicate

Making the grade: The sensitivity of education program effectiveness to input choices and outcome measures - Kerwin, Jason T.; Thornton, Rebecca L. (The Review of Economics and Statistics, 2021)
This paper demonstrates the acute sensitivity of education program effectiveness to the choices of inputs and outcome measures, using a randomized evaluation of a mother-tongue literacy program. The program raises reading scores by 0.64 SD and writing scores by 0.45 SD. A reduced-cost version instead yields statistically insignificant reading gains and some large negative effects (−0.33 SDs) on advanced writing. We combine a conceptual model of education production with detailed classroom observations to examine the mechanisms driving the results; we show they could be driven by the program initially lowering productivity before raising it, and potentially by missing complementary inputs in the reduced-cost version.

The Impact of Teacher Effectiveness on Student Learning in Africa - Buhl-Wiggers, Julie; Kerwin, Jason; Smith, Jeffrey; Thornton, Rebecca (Rise Programme, 2017)
Teaching quality is known to be critical for students’ education and life prospects in developed countries. However, little is known about how teacher quality affects student learning in Africa. This paper presents the first estimates of teacher value-added from an African country, using data from a school-based RCT in northern Uganda. Exploiting the random assignment of students to classrooms within schools, we estimate a lower bound on teacher effects. A 1-SD increase in teacher quality leads to at least a 0.14 SD improvement in student performance on a reading test at the end of the year. Shifting teachers from the 10th to the 90th percentile of quality increases performance by 0.36 SDs –comparable to the most effective education interventions conducted in Africa. Our results also suggest that an increase in teacher quality can make other education interventions more efficient.
Keywords: C:Uganda; NULP